Isolation, purification, structure elucidation, and antibody recognition of two phospholipases A2 and Crotoxin variation in the venom of the Tamaulipan rattlesnake Crotalus morulus - Mejía-Sánchez, Miguel Angel; Cardoso-Arenas, Samuel; Miranda-Blancas, Ricardo; Franco-Vásquez, Adrián Marcelo; Carbajal-Saucedo, Alejandro; Olamendi-Portugal, Timoteo; Zamudio, Fernando; Arreguín-Espinosa, Roberto; Corzo, Gerardo (Acta tropica, 2025)
•Antibodies against Crotoxin subunit B revealed large variability of this protein in individual venoms of C. morulus.•The primary structures of a new Crotoxin B and a Lys49 PLA2 were elucidated.•The Crotoxin subunit B from C. morulus has an LD50 of 0.83 μg/g of mice.•Commercial antivenoms did not neutralize the enzymatic activity of Crotoxin B from C. morulus. The venom of six individuals of Crotalus morulus, an unstudied endemic species of Mexico, was analyzed by anti-crotoxin antibodies (anti-rCrotxB and anti-rCrotxAB) obtained from recombinant expression of crotoxin B and of a tandem protein containing both crotoxin A and B, to discern which individuals from the species C. morulus contain crotoxin. As a result, two new phospholipases were identified from only one of the six individuals named C. morulus 1032, which had the most toxic venom with a low median lethal dose (LD50 < 40 μg/20 g mouse). RP-HPLC fractionation and a combination of Edman degradation and endoproteolytic cleavages elucidated the primary structure of such phospholipases. The assigned names were Cm-PLA2–1 and Cm-PLA2–2, respectively. Cm-PLA2–1 is a phospholipase type A2 that showed neurotoxic activity towards mice with an LD50 value of 16.6 μg/20 g mouse. Cm-PLA2–1 is 92 % identical to crotoxin B from the venom of Crotalus durissus terrificus. The second phospholipase type A2, Cm-PLA2–2, did not cause lethality or any apparent signs of toxicity in mice when injected by the intravenous route up to a dose of 30 μg/20 g mouse. Two commercial antivenoms and anti-crotoxin B could not inhibit the enzymatic activity of Cm-PLA2–1; however, they neutralize the venom of C. morulus 1032 with an ED50 of < 40 mg antibody/mg venom. Identification of crotoxin-like toxins in rattlesnake species is essential to understanding the mechanisms of envenomation of these crotalids, since some individuals have more toxic venom than others. Therefore, concerning crotalid antivenoms, attention must be paid to selecting species with crotoxin to be used as immunogens. This work provides information for future research on their crotalid toxicity and effects on humans.